8b+3-10=-2(b-2)+3

Simple and best practice solution for 8b+3-10=-2(b-2)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8b+3-10=-2(b-2)+3 equation:


Simplifying
8b + 3 + -10 = -2(b + -2) + 3

Reorder the terms:
3 + -10 + 8b = -2(b + -2) + 3

Combine like terms: 3 + -10 = -7
-7 + 8b = -2(b + -2) + 3

Reorder the terms:
-7 + 8b = -2(-2 + b) + 3
-7 + 8b = (-2 * -2 + b * -2) + 3
-7 + 8b = (4 + -2b) + 3

Reorder the terms:
-7 + 8b = 4 + 3 + -2b

Combine like terms: 4 + 3 = 7
-7 + 8b = 7 + -2b

Solving
-7 + 8b = 7 + -2b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '2b' to each side of the equation.
-7 + 8b + 2b = 7 + -2b + 2b

Combine like terms: 8b + 2b = 10b
-7 + 10b = 7 + -2b + 2b

Combine like terms: -2b + 2b = 0
-7 + 10b = 7 + 0
-7 + 10b = 7

Add '7' to each side of the equation.
-7 + 7 + 10b = 7 + 7

Combine like terms: -7 + 7 = 0
0 + 10b = 7 + 7
10b = 7 + 7

Combine like terms: 7 + 7 = 14
10b = 14

Divide each side by '10'.
b = 1.4

Simplifying
b = 1.4

See similar equations:

| 9+2x=2x+6 | | 3x+137+2x+28=180 | | -2+5k=15-4k | | 7x+17-6x=-3-10 | | 2x^2-2=-202 | | 2x+8=42 | | (p^5+3p^3-3p-1)(p^5-3p^3-3p+1)=0 | | -8(x-6)+2=90 | | -2x=1-(-1) | | .16t-.8=.2 | | 28=7xn | | 3(-2+3x)=-9x-4 | | 12(x-5)=-6-6 | | 4x+10=6x+200 | | -3(2-3h)=-3 | | r=4n+4u | | -5(1-7a)=19 | | 9-3a=12 | | 2x+10=x+20 | | 41y=8(5y-7) | | 2(x+2)=-x-17-4x | | 5x+(x+6)=-34-2x | | 8x-2(x-5)=6x+2 | | 2z^2+12z=0 | | 4(k-6)-3(k+2)=-5 | | 7x+8-6x=10 | | (x^3+x^2+x-1)(x^3-x^2+x+1)=0 | | 2z^2+12=0 | | 55+35= | | 1/4(2x-16)=3x+11 | | 7+5s-1=9s+33-7s | | -3r=3r-54 |

Equations solver categories